2023
DOI: 10.1017/s0956536121000432
|View full text |Cite
|
Sign up to set email alerts
|

Special Section Introduction: Introducing Zacapu archaeology and the Uacusecha project

Abstract: According to Purepecha oral tradition, the ancestors of the Uacusecha dynasty that ruled Michoacan at the beginning of the sixteenth century began their epic in the Zacapu region. The importance of this region also lies in the research carried out since the early 1980s that led to the elaboration of a regional sequence outlining the trajectory of pre-Hispanic societies centuries before the emergence of the Tarascan state. New research carried out on the area since 2009 has clarified this reference framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The Middle Postclassic agricultural pattern is different and is thus consistent with the winds of change that came at that time with the newcomers (Michelet et al 2005; Pereira 2023). Some of the volcanic ash soils on Late Pleistocene lava flows valued by Epiclassic farmers remained exploited by Milpillas phase populations.…”
Section: Results: Evolution Of the Agricultural Landscapementioning
confidence: 61%
See 2 more Smart Citations
“…The Middle Postclassic agricultural pattern is different and is thus consistent with the winds of change that came at that time with the newcomers (Michelet et al 2005; Pereira 2023). Some of the volcanic ash soils on Late Pleistocene lava flows valued by Epiclassic farmers remained exploited by Milpillas phase populations.…”
Section: Results: Evolution Of the Agricultural Landscapementioning
confidence: 61%
“…Digital and fieldwork have made it possible to revise the cultural evolution of the area from the seventh to the fifteenth century (Dorison 2019:346–507). For more detail on each chronological phase, we invite the reader to refer to other articles in this Special Section (Forest 2023; Lefebvre et al 2023; Pereira et al 2023), while we focus here on results concerning the landscape and its management for agriculture through time.…”
Section: Results: Evolution Of the Agricultural Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1980s, several studies have investigated the possible origins of this population through regional diachronic observation of changes in settlement patterns (Castañeda et al 2020; Faugère 2007; Michelet et al 2005; Pereira et al 2005). These studies suggested that the Zacapu Malpaís populations derived from local groups as well as populations migrating from both further north in Michoacan and from south of Guanajuato (see Pereira 2023). The causes of this migration and aggregation remain unclear, although the north-to-south movement of the population might be associated with environmental changes occurring on the northern Mesoamerican border (Armillas 1969; Beekman 2010, 2012; Domínguez and Castro López 2017).…”
mentioning
confidence: 98%